Uncovering the Impact of Profitability, Liquidity, Activity, and Leverage on Share Prices - Novriyanti, Indira (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose of this study is to determine and analyze the profitability of liquidity, activity, and leverage together to affect stock prices. The method used by the authors in this study is quantitative associative method. The population obtained is as many as 16 pharmaceutical and cosmetic companies. The sample selection was carried out by purposive sampling method, samples used by 11 pharmaceutical and cosmetic companies that reported their companies' financial statements on the Indonesia Stock Exchange (IDX). The analysis tool to be used in this study is eviews 12. The data analysis techniques used in this study are, hypothesis test, partial test, determination coefficient test, moderated regression analysis test. The results showed simultaneously that profitability, liquidity, activity and leverage had a significant effect on the stock price by 83.9219%, the remaining 16.0781% was influenced by other factors not explained in this study.